Pengaruh Kepemimpinan Transformasional Dan Kompensasi Terhadap Kinerja Karyawan PT. PLN (Persero) UPJ Semarang - Tria Mondiani (Jurnal Administrasi Bisnis, 2012)
This research aims to analyze the influence of transformational leadership and compensation towards employee performace at PT PLN (Persero) UPJ Semarang. The population of this research is all 95 employees of PT. PLN (Persero) UPJ Semarang. Saturation sampling technique was used to determine the sample. Data analyzed using multiple linear regression analysis. Based on the analysis, it can be concluded that: (a) transformational leadershid gives positive impact upon employee performance. The impact given by transformational leadershid upon employee performance is 14.5%; (b) compensation brings positive influence upon employee performance as much as 14.9%; (c) transformational leadership and compensation significantly influence employee performance with coeficient of determination of 29.7%. It is suggested that the leader be more active and vigorous in giving individual consideration, improving regulations and socializing compensation policy to the employes to avoid mistakes, conducting training and development, and giving reward to employees who have good achievement.